Unavoidability of Sino-American rift: History of strategic decoupling - Bajrektarevic, Anis H (AEI Insights, 2021)
Does our history only appear overheated, while it is essentially calmly predetermined? Is it directional or conceivable, dialectic and eclectic or cyclical, and therefore cynical? Surely, our history warns (no matter if the Past is seen as a destination or resource). Does it also provide for a hope? Hence, what is in front of us: destiny or future? Theory loves to teach us that extensive debates on what kind of economic system is most conductive to human wellbeing is what consumed most of our civilizational vertical. However, our history has a different say: It seems that the manipulation of the global political economy (and usage of fear as the currency of control) – far more than the introduction of ideologies – is the dominant and arguably more durable way that human elites usually conspired to build or break civilizations, as planned projects.